PELAKSANAAN METODE PEMBELAJARAN PKN MENGGUNAKAN MEDIA GAMBAR DI MI NURUL HUDA - dedeh setiasih; Muthli'ah; Afiyatun Kholifah (IAIC (Institut Agama Islam Cirebon), 2021)
ABSTRACT This research was conducted at MI Nurul Huda with the aim of describing the application of Civics learning methods by using picture media to improve the activities and learning outcomes of fifth graders in Civics learning themes adapted to KI and KD. The problem that becomes the background of this research is that students tend to be passive, because there is less interaction between students and teachers, the teacher is more focused on lectures so that students only listen during the learning process and the learning outcomes of class V students are still not good. This research is a qualitative research that uses a descriptive approach. Describing a phenomenon according to the actual situation experienced by the research subject, in this study the researcher wanted to describe how the Civics learning method used image media at MI Nurul Huda. Sources of research data how many observations and interviews. The results showed that the image media was effectively used in Civics learning and made students' learning motivation increase. Keyword : Civic Education Learning, Picture Media, Student Motivation of MI Nurul Huda